Design of User Interfaceâs Prototype and Simulator of Asymmetric Bridge Converter for 12 Slots 8 Poles 5kW 3000 RPM Switched Reluctance Motor Drive - Hamdan Rivani, Naufal
Three-wheeled low power vehicle is often used in micro, small, and small enterprise. To power up the vehicle, fossil fuels which can cause air pollution is still preferably used. To reduce the dependence of fossil fuels, a change of prime mover in this vehicle into electric-based vehicle utilizing Switched Reluctance Motor is proposed. The Switched Reluctance Motor is used since it has simple construction, cheap, and reliable. The conversion of vehicle’s prime mover into Switched Reluctance Motor will affect the user interface of the vehicle, thus it also demands change in its user interface. In this final project, a prototype design and simulator of asymmetric bridge converter’s user interface driving SRM will be conducted. Sensors used in this user interface are Hall effect current sensor, Hall effect sensor for position and speed sensing, resistive voltage divider for voltage sensing, and thermistor for temperature sensing. After choosing those sensors, some signal conditioning circuits, such as dc level shifter, filter, and attenuation are designed to make the output of sensors compatible with DSP’s input specification. Next, power supply circuits, such as 1.8V, 3.3V, ±5V, and ±15V are chosen to meet the supply voltage’s specification of the sensors and signal conditioning circuit. Last, a design of simulator’s user interface for Asymmetric Bridge Converter which can accommodate user’s input as well as display the vehicle’s status had been implemented and simulated to run the simulation of electric vehicle powered by 12 Slots 8 Poles 5kW 3000 rpm Switched Reluctance Motor.